TOLERANCE AS A POLITICAL AND SOCIAL GUIDELINES FOR THE DEVELOPMENT AND SELF-REGULATION OF SOCIETY - Кушніренко, І.Ю. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
This article analyzes the tolerance as a political and social phenomenon. The basic aspects of tolerance as an essential attribute of a democratic society. Argued fact relevance tolerance for self-regulation of society at all stages of its development. Proposed way to eliminate the shortcomings of the Ukrainian national policies and legislation to improve the level of tolerance in the country.